Short Communication: The impact of Gamma radiation on Tdc and Str gene expressions in Catharanthus roseus regenerated plantlets (Biodiversitas Journal of Biological Diversity, 2018)
Noormohammadi Z, Taban M, Farahani F. 2018. Short Communication: The impact of Gamma radiation on Tdc and Str gene expressions in Catharanthus roseus regenerated plantlets. Biodiversitas 19: 1805-1810. Catharanthus roseus L.G. Don, is the essential medicinal plant with considerable attention. This plant is a rich source of terpenoid indole alkaloids (TIAs). The main alkaloids in C. roseus are vinblastine, vincristine, and ajmalicine. The tryptophan decarboxylase (Tdc) and Strictosidine synthase (Str) are key enzymes in TIA biosynthesis. In the present study, Tdc and Str gene expressions, as well as vinblastine production were evaluated in tissue culture regenerated plantlets in 4 groups; control, 60 Gy irradiation, 50 mg/L putrescine and 60 Gy irradiation + 50mg/L putrescine treatments. The results revealed significant increase in Tdc and Str gene expressions in 60 Gy irradiation + 50mg/L putrescine treated plantlets in comparison with control samples by using qPCR methods. HPLC analysis showed a higher amount of vinblastine in 60 Gy + 59 mg/L putrescine treated plantlets. Gamma radiation and putrescine as elicitor and polyamine, respectively, are able to improve vinblastine production in C. roseus.
Keywords: Gene expression; periwinkle; radiation; secondary metabolism; tissue culture